FAMILY ASILIDAE - Wolff, Marta; Lamas, Carlos José Einicker (Zootaxa, 2016)
Asilidae is one of the largest Diptera families with more than 7,000 recognized species worldwide. All their species are predators on arthropods, mainly insects. This catalogue presents 71 species distributed in 26 genera, ten tribes or generic groups and four subfamilies. For each species we present the available geographical information and relevant references.